Personal empowerment of student activities for Future University students - Hassan, Prof. Dr. Thaer Rashid (Sulaimani Journal for Humanities, 2025)
This research aims to develop a personal empowerment scale for student activities and to identify the role of student activities in enhancing the empowerment and participation of Future University students. The researcher adopted a descriptive approach using a survey methodology. The research population and sample consisted of Future University students during the 2023-2024 academic year. The research sample comprised (275) male and female students randomly selected from (11) colleges. Among the most important conclusions are that student activities play a pivotal role in developing students' leadership skills and help them gain confidence and learn through experience. Participation in student activities enhances communication and cooperation skills among students, increasing their ability to work effectively within multidisciplinary teams. Student activities also strengthen students' sense of belonging to the university community, contributing to improving their overall university experience. Key recommendations include the necessity of providing training programs and initiatives aimed at developing students' leadership skills to ensure they benefit fully from student activities, the importance of establishing effective and continuous communication channels between university administration and students to promote the announcement of student activities and events, and the need to offer a diverse range of activities. Student activities to meet the interests of all students, including academic, sports, scouting, cultural, and social activities.
Keywords: Empowerment; Activities; Students; University